Therapeutic Effect of Barberry (Berberis vulgaris) Root Extract on Experimental Cutaneous Leishmaniosis in a BALB/c Mouse Model - Sadegh Shirian; Morteza Norouzi Cholcheh; Saeed Habibian Dehkordi; Behnam Bakhtiari Moghadam (Veterinary Medicine and Science)
ABSTRACT The bioactive compounds derived from plants offer promising avenues for discovering new treatments for various types of leishmaniasis. Approximately 22 alkaloids have been identified in different parts of the barberry plant, particularly in the roots. This study aimed to investigate the therapeutic effects of barberry (Berberis vulgaris) on the treatment of experimental cutaneous leishmaniasis (CL) caused by Leishmania major in a BALB/c mouse by using pathological, immunohistochemical, and clinical methods. Thirty BALB/c mice, aged 6–8 weeks, were purchased from the Razi Animal Laboratory at Karaj Institute and allowed for adaptation by 1 week. The mice were divided into three groups including control, treatment, and vehicle groups. Animals of both treatment and vehicle groups received a subcutaneous injection of 0.1 mL culture medium containing 2 × 106 promastigotes at the base of their tails. The vehicle and treatment groups received Vaseline alone and barberry root extract mixed (as ointment) in Vaseline, respectively. The intact mice were used as the control group without any intervention. After 32–35 days, the wounds were formed at the injection sites. The extract ointment was applied to treat the wounds three times daily for 28 days. The wound diameters were measured on days 7, 14, 21, and 28 post‐treatments, and the skin tissue samples were investigated using haematoxylin and eosin staining. Clinical evaluations revealed that the wound size was significantly decreased in the treatment group compared to the controls (p < 0.05). The treatment group also exhibited lower Leishmania parasite loads than other groups. Unlike the expression of TGF‐β, the mean level of IL‐1 and IL‐6 was significantly increased (p < 0.001) in the treatment group compared to other groups. These findings suggest that Berberis vulgaris can effectively improve skin lesions caused by L. major by modulating inflammatory responses in the BLAB/c mouse model.